Anti-endothelial cell antibodies, endothelial proliferation and von Willebrand factor antigen in Behçet's disease - (:unkn) unknown (Springer-Verlag, 1995)
Endothelial cell dysfunction has previously been demonstrated in Behçet's disease which has vasculitic features. In this study we investigated antiendothelial cell antibodies (AECA) and von Willebrand factor antigen (vWF) levels in patients with Behçet's disease. In vitro effects of patient sera on endothelial cell proliferation were also evaluated. AECAs were present in 29% of 70 Behçet's disease patients (Binding Index:25±29% vs 9±7% in normal controls, p<0.005). 95% of AECA positive patients were clinically active compared to 74% of AECA negative patients (p=0.04). Among specific organ manifestations only active arthritis correlated with AECA positivity (6 of 7 patients vs 14 of 63, p=0.002). AECA positive patients had a significantly higher mean ESR (37±24 mm/h vs 21±17 mm/h, p:0.006). Mean vWF levels were also significantly higher in patients compared to controls (166±75% vs 84±34%, p.<0.0001). No correlations were observed between AECA titres and vWF levels. No significant differences were observed between patients and controls when endothelial cell proliferation was studied (Proliferation Index: 1.25±0.28 vs 1.12±0.25, p=0.5). Our results suggest that AECA may be related to disease activity in Behçet's disease. The presence of vWF, even in patients in complete remission, might be related to factors other than endothelial damage for vWF release from endothelial cells. © 1995 Acta Medica Belgica.
Keywords: Anti-endothelial Cell Antibodies; Behçet's Disease; von Willebrand Factor Antigen